Implementation of a pharmacogenomics education program for pharmacists. (1st December 2018) - Formea, Christine M.; Nicholson, Wayne T.; Vitek, Carolyn Rohrer; Wix, Kelly K.; McCullough, Kristen B.; Cunningham, Julie L.; Zeuli, John D.; Matey, Eric T.; Merten, Julianna A.; Richardson, Darcy M.; Billings, Andrea L.; Schramm, Garrett E.
Abstract: Purpose: The development, implementation, and evaluation of a pharmacogenomics education program for pharmacists in a large, integrated multicampus health system are described. Summary: Pharmacogenomics has been described as tailoring medications to each patient's unique genetic sequence with the goals of minimizing harmful effects and optimizing therapeutic effects. Pharmacists are uniquely trained to lead the implementation of pharmacogenomics in clinical care. After assessment of pharmacists' comfort with pharmacogenomics, different approaches were explored to develop, pilot test, and disseminate pharmacogenomics education across a multicampus academic medical center. Limited success with large-audience, single-lecture didactic education led to development and delivery of targeted, competency-based online modules using the institution's academic virtual learning environment and course management system. Implementation steps included (1) collaboration with the Mayo Clinic Center for Individualized Medicine to create an interprofessional development team and project charter, (2) galvanizing pharmacy leadership support across multiple campuses, (3) development of competency-based interactive modules, and (4) assessment of the quality of and learner satisfaction with the modules. Significant improvements in competency scores were observed with each module and across the multiple campuses. Satisfaction with the education program was assessed at the end of a 4-module series. Conclusion: A pharmacogenomics educational program targeting pharmacists was developed through interprofessional collaboration and provided a novel opportunity to construct an educational infrastructure to support enterprise health-system campuses with limited educational resources.